2010
DOI: 10.1002/chem.201000318
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Monitoring of Mass‐Transport‐Related Enzymatic Reaction Kinetics in a Nanochannel‐Array Reactor

Abstract: To understand the fundamentals of enzymatic reactions confined in micro-/nanosystems, the construction of a small enzyme reactor coupled with an integrated real-time detection system for monitoring the kinetic information is a significant challenge. Nano-enzyme array reactors were fabricated by covalently linking enzymes to the inner channels of a porous anodic alumina (PAA) membrane. The mechanical stability of this nanodevice enables us to integrate an electrochemical detector for the real-time monitoring of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Recently, we used porous anodic alumina (PAA) with a size‐defined nanochannel array to investigate both the confinement of enzyme reaction kinetics and the molecule diffusion behavior. We found that the reaction kinetics changes from a kinetically controlled process at low transport rates of the substrate to a diffusion‐limited one at higher substrate transport rates 8. In that report, the size of the nanochannels was relatively large (200 nm in diameter), and thus the confinement effect of the enzyme reaction kinetics was not that significant.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Recently, we used porous anodic alumina (PAA) with a size‐defined nanochannel array to investigate both the confinement of enzyme reaction kinetics and the molecule diffusion behavior. We found that the reaction kinetics changes from a kinetically controlled process at low transport rates of the substrate to a diffusion‐limited one at higher substrate transport rates 8. In that report, the size of the nanochannels was relatively large (200 nm in diameter), and thus the confinement effect of the enzyme reaction kinetics was not that significant.…”
Section: Introductionmentioning
confidence: 76%
“…Herein, four nanochannels with a length of 1.2 cm, a width of 200 μm and heights of 55, 80, 110 or 140 nm are fabricated and used as the confined enzyme reactors. Since substrate transport considerably affects the enzyme reaction kinetics,8, 18 a constant flow rate of the glucose substrate was kept during the measurements (for the detailed process, see the Supporting Information, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, glucose oxidase has demonstrated a sevenfold reduction in activity upon covalent immobilization on a porous alumina support compared with the activity in the homogeneous (bulk) phase. [21] Further to reports on catalase immobilization on various supports, [22] our approach allows for the tuning of product yield through variation of residence time (t) in membrane pores. The residence time was calculated as t = V/(AJ V ), where V is the membrane volume, A the external area (33.2 cm 2 ), and J V the permeation flux (cm 3 cm 2 s À1 ) through volume V. In addition, V = eAL, where e is the porosity (70 % average, from manufacturer's data) and L the membrane thickness (125 mm).…”
Section: Stacked Membranes For Enzymatic Catalysismentioning
confidence: 99%
“…Problems with the instability of biological ion channels underi nv itro conditions, still trouble their utilizationi nr eal environments. [5] Thus,f abricatingasmart artificial channel with the ability of mimicking the biological process of NO-regulated ion transport is highly demanded, which will greatly expand the applications of gas-drivens ystems for real-world applications.…”
mentioning
confidence: 99%